2001
DOI: 10.1021/bi010665t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Basis for the Increased Thermostability of CheY from the Hyperthermophile Thermotoga maritima

Abstract: The CheY protein isolated from the hyperthermophile Thermotoga maritima is much more resistant to thermally induced unfolding than is its counterpart from the mesophile Bacillus subtilis. To determine the basis of this increased thermostability, the temperature dependence of the free energy of unfolding was determined for these CheY homologues using denaturant-induced unfolding experiments. This allowed comparison of T. maritima CheY with B. subtilis CheY and determination of the thermodynamic qualities respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Of the five thermodynamically characterized thermophile-mesophile protein pairs, four thermophilic proteins have up-shifted and broadened stability curves compared with their mesophilic homologs (8,(22)(23)(24)(25). It is difficult to make conclusions based on this limited data set, but it is possible that a large group of enzymes and other proteins requiring a finely tuned energy landscapes use lower ⌬Cp°values to balance a high melting temperature with the thermodynamic stability needed for optimal activity.…”
Section: Construction and Purification Of Variant Rnases Hmentioning
confidence: 99%
“…Of the five thermodynamically characterized thermophile-mesophile protein pairs, four thermophilic proteins have up-shifted and broadened stability curves compared with their mesophilic homologs (8,(22)(23)(24)(25). It is difficult to make conclusions based on this limited data set, but it is possible that a large group of enzymes and other proteins requiring a finely tuned energy landscapes use lower ⌬Cp°values to balance a high melting temperature with the thermodynamic stability needed for optimal activity.…”
Section: Construction and Purification Of Variant Rnases Hmentioning
confidence: 99%
“…Equilibrium denaturation studies have provided detailed knowledge of the structure, stabilization, and folding of small, monomeric proteins [13,14]. Thermodynamic comparison of mesophilic and thermophilic ribonuclease H revealed that the heat capacity of unfolding of the thermophilic enzyme is lower than that of its mesophilic counterpart, although the proteins have maximal stabilities at similar temperatures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic comparison of mesophilic and thermophilic ribonuclease H revealed that the heat capacity of unfolding of the thermophilic enzyme is lower than that of its mesophilic counterpart, although the proteins have maximal stabilities at similar temperatures [13]. For two small single-domain CheY homologues from Thermotoga maritima and Bacillus subtilis, it was found that the enhanced thermostability of the former is a direct result of the increased enthalpy contribution at the temperature of zero entropy, T s , and the decreased heat capacity change upon unfolding [14]. In addition, the dimeric serine hydroxymethyltransferases from B. subtilis and Geobacillus stearothermophilus followed different unfolding paths despite having a high degree of sequence identity [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to study the change in intemal dynamics under the influence of various perturbations. Temperature is one of the important factors, since it can provide a probe of many aspects such as protein stability, protein folding, and ligand binding [11][12][13][14], as well as ah experimental means for investigating the energy landscape [15]. The temperature dependence of iSN autorelaxation rates in the backbone have been studied for a number of proteins [13,14,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%